2020
DOI: 10.1136/ejhpharm-2020-002449
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing practices of lopinavir/ritonavir, hydroxychloroquine and azithromycin during the COVID-19 epidemic crisis and pharmaceutical interventions in a French teaching hospital

Abstract: Objective The aims of this study were to describe prescribing practices of lopinavir/ritonavir, hydroxychloroquine and azithromycin during the COVID-19 epidemic crisis (primary endpoint), then to characterise pharmaceutical interventions (PIs) targeted to these medications and evaluate the impact of these PIs on prescribers' practices (secondary end-points). Methods This retrospective observational study was carried out at the University Hospital of Strasbourg (France) from March to April 2020. The analysed po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…Beyond the medication effects, several cardiac manifestations have been described in patients with COVID-19 including acute myopericarditis, acute coronary syndrome, congested heart failure, cardiogenic shock, and cardiac arrhythmias as a result of the injuries caused by the virus and systemic inflammation [ 287 ]. These cardiac manifestations were not only shown with CQ or HCQ use, but also with other drugs used in the treatment of COVID-19 such as corticosteroids, rivabirin, LPVr, and AZM [ 288 , 289 , 290 , 291 ]. This suggests that COVID-19 could have a role in these cardiac safety reports.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the medication effects, several cardiac manifestations have been described in patients with COVID-19 including acute myopericarditis, acute coronary syndrome, congested heart failure, cardiogenic shock, and cardiac arrhythmias as a result of the injuries caused by the virus and systemic inflammation [ 287 ]. These cardiac manifestations were not only shown with CQ or HCQ use, but also with other drugs used in the treatment of COVID-19 such as corticosteroids, rivabirin, LPVr, and AZM [ 288 , 289 , 290 , 291 ]. This suggests that COVID-19 could have a role in these cardiac safety reports.…”
Section: Discussionmentioning
confidence: 99%
“…This was also the primary DRP reported in a study wherein the objective was to compare pharmaceutical interventions in patients with and without .6%, respectively) (Perez et al, 2020). However, a separate study observed that only 10.2% of the 59 pharmaceutical interventions performed in patients with COVID-19 treated with lopinavir/ritonavir, hydroxychloroquine or azithromycin were related with an incorrect dosage; wrong duration of treatment (54.2%) and the presence of interactions (23.7%) comprised the main DRPs (Gourieux et al, 2021). Frontiers in Pharmacology frontiersin.org…”
Section: Discussionmentioning
confidence: 99%
“…In one study done in a French university hospital, 28.8% of patients with COVID-19 presented at least one DRP during a 1-month study period ( Perez et al, 2021 ). Another study noted that 19.1% of patients with COVID-19 treated with lopinavir/ritonavir, hydroxychloroquine or azithromycin presented at least one DRP in relation to those drugs ( Gourieux et al, 2021 ). The rate of DRP observed in patients with COVID-19 was higher than in other previous studies carried out in patients without COVID-19 ( Ferrández et al, 2019 ) ( Ferrández et al, 2018 ) ( Krähenb et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations